A role for helminth parasites in achieving immunological tolerance in transplantation. (26th February 2015) - Johnston, Chris; McSorley, Henry; Smyth, Danielle; Anderton, Stephen; Wigmore, Stephen; Maizels, Rick
Abstract: Background: Helminths infect more than a quarter of the world's population. Their success as parasites is the result of active immunomodulation of the host immune response, which can have benefits for the host, particularly in suppressing harmful allergic and autoimmune responses. Accordingly, we tested the hypothesis that helminth infection reduces the immune response to allograft transplantation. Methods: C57BL/6 mice were implanted with a subcutaneous minipump that delivered a continuous infusion of secreted products from the model mouse intestinal parasite, Heligmosomoides polygyrus (equivalent to 7 μg of protein per day). Simultaneously, fully allogeneic skin grafts from BALB/c donors were performed. 7 days later, lymphocytes were isolated from allograft draining lymph nodes and analysed by flow cytometry. Findings: Flow cytometric analysis showed a 41·7% increase in the mean percentage of CD4+CD25+Foxp3+ regulatory T cells (of total CD4 cells) from a baseline of 8·1% (95% CI 7·4–8·8) in untreated mice to 11·5% (8·8–14·2) in the treatment group (p=0·0085). Treatment with parasite products also increased mean expression of the regulatory cell surface receptor PD1 by 62·2% in the effector CD4 T-cell population from a baseline of 7·7% (5·7–9·6) to 12·5% (7·5–17·4) (p=0·03). Interpretation: The results show that helminth-derived products can powerfully induce regulatory immunological mechanisms in the presence of a fully allogeneic transplant. Identification of the specific mechanisms involved in suppression of allograft rejection by helminth parasites could lead towards development of safe and effective novel therapeutic strategies. Funding: Wellcome Trust.